Interference of SARS-CoV-2 with other Respiratory Viral Infections agents during Pandemic - A. A. Sominina; D. M. Danilenko; K. A. Stolyarov; L. S. Karpova; M. I. Bakaev; T. P. Levanyuk; E. I. Burtseva; D. A. Lioznov (Эпидемиология и вакцинопрофилактика)
Background. Integrative epidemiological and etiological analysis of peculiarities of the development of the COVID-19 pandemic in different countries of the world is of significant scientific and practical interest in order to improve the preparedness of medical and social services during the upcoming pandemics. The purpose of the research. To determine the features of the epidemic process caused by a new coronavirus infection COVID-19, in all the diversity of its interaction with influenza viruses and other ARVI agents in the Russian Federation.Materials and methods. The studies were performed in the system of routine influenza surveillance by the Federal Center for Influenza and ARI at the Smorodintsev Research Institute of Influenza and the Center for Ecology and Epidemiology of Influenza at the National Center for Epidemiology and Microbiology named after N.F. Gamaleya, in cooperation with Regional Collaborating Base Laboratories in accordance with the Order of the Federal Service for Consumer Rights Protection Surveillance and Human Well-being No. 373 of March 31, 2005. Information on morbidity and hospitalization was provided by the erritorial Departments of Rospotrebnadzor. Information on the results of PCR detection of influenza and ARVI viruses, including SARS-CoV-2, was received from the «enters for Hygiene and Epidemiology" and was entered on-line into the electronic database of the Smorodintsev Research Institute of Influenza of the Ministry of Health of Russia. «AmpliSens reagent kits produced by the Central Research Institute of Epidemiology were used for PCR detection and subtyping of influenza A and B viruses, to identify ARVI agents, for PCR diagnosis of COVID-19 the kits certified in the Russian Federation of various producers were used.Results. It has been established that the annual epidemics of influenza, as well as the development of the second wave of the COVID- 19 pandemic in the season 2020–2021 was preceded pronounced increase of incidence rate (55.0 - 67.9 per 10,000), associated with rhinoviruses activity, starting from the week 38 to week 43. 2020, which reached on the peak 23–29.0% of patients examined. The increase of COVID-19 activity in the fall of 2020 began from week 41 with the peak (26.6–31.3%) of detection in the period from the week 47.2020 to week 4. 2021. The duration and severity of COVID-19 diseases, requiring hospitalization, distinguished the SARS-CoV-2 pandemic from influenza epidemics/pandemics. Significant changes in the nature of the epidemic process were found in the analysis of the age structure of morbidity and hospitalization – their distinct decrease in children's age groups against the background of pronounced growth among patients of the age group 15–64 yrs and, especially, in elderly people ≥ 65 yrs. The incidence growth curves coincided in time with an increase in SARS-CoV-2 activity against the background of a decrease in the detection frequency of other ARVI pathogens, including influenza and RSV viruses, as a result of pronounced interference between pathogens. Interestingly, as the frequency of SARS-CoV-2 detection decreased to 15–19%, the activity of rhinoviruses, seasonal coronaviruses and metapneumoviruses began to increase again from 0.7–3.0% to 5.6–6.6%, which indicated the existence of a quantitative relationship between the interference indicators of SARS-CoV-2 with other ARI agents. It was most clearly manifested in relation to influenza and RSV viruses, which detection in general for the season dropped to 0.04% and 0.3% respectively.Conclusions. The phenomenon of interference of SARS-CoV-2 with other viral respiratory agents was established, based on the facts of a sharp suppression of the circulation of influenza viruses, respiratory syncytial virus and other ARVI pathogens during the period of active spread of the pandemic coronavirus. A distinctive feature of the SARS-CoV-2 pandemic, in comparison with influenza epidemics, was its long duration and the severity of the diseases caused by that virus. During the period of the pandemic, a clear decrease in the incidence and hospitalization among children was revealed, with their pronounced growth in adults and, especially, in older people ≥ 65 years old.